2018
DOI: 10.1039/c8ra00975a
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone protects against cardiac damage from doxorubicin-induced heart failure in Sprague-Dawley rats

Abstract: Heart failure is a complex end stage result of various cardiovascular diseases, and has a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In terms of tissue fibrosis, 5 studies that model the tissue fibrosis of different organs were included. For cardiac fibrosis, one study using doxorubicin-induced rats was included [38]. For lung fibrosis, 2 studies with bleomycin-induced rats [23] and paraquat-induced rats [42] were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of tissue fibrosis, 5 studies that model the tissue fibrosis of different organs were included. For cardiac fibrosis, one study using doxorubicin-induced rats was included [38]. For lung fibrosis, 2 studies with bleomycin-induced rats [23] and paraquat-induced rats [42] were included.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of thymoquinone has been shown to have anti-fibrotic and anti-apoptosis effect in this study. The study revealed the potential of thymoquinone as cardioprotective agent for myocardial fibrosis [38].…”
Section: Resultsmentioning
confidence: 99%
“…Rats treated with TQ before ISO administration exhibited less brous tissue deposition in the myocardium as indicated by the histopathological examination of cardiac sections, compared to the vehicle-pretreated ISO group. The mechanism of this effect may be related to the TQinduced downregulation of the expression of the protein levels of transforming growth factor beta, collagen I, collagen III and α-smooth actin that play a crucial role in the pathogenesis of myocardial brosis (Bujak and Frangogiannis 2007;Pei et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is the main active ingredient derived from Nigella sativa seeds, commonly used as a food supplement and in folk medicine (Ahmad et al 2013). Thymoquinone reduces the generation of reactive oxygen species (ROS) and suppresses oxidative stressinduced oxidative damage in several tissues as in cyclosporine A-induced nephrotoxicity (Farag et al 2015), acetaminophen-induced hepatotoxicity (Awad et al 2016) and doxorubicin-induced cardiotoxicity (Pei et al 2018). Thymoquinone is regarded by many investigators as a potent antioxidant with additional anti-in ammatory properties that may expand its therapeutic potential especially in cardiovascular diseases (Shabana et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Doxorubicin hydrochloride (Dox), a chemotherapeutic drug, which intercalates with DNA, is used for a wide range of cancer treatments [ 4 , 5 ], however it is associated with severe side effects, e.g., cardiac damage, vomiting, bone marrow suppression, tissue damage at the site of injection, and myelosuppression, which prevent it from being the prominent first choice [ 6 , 7 ]. Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL), a protein considered as a promising candidate for treatment owing to its selective apoptotic effect on cancer cells [ 8 , 9 ], is not therapeutically effective, as IV administration leads to insufficient amount at the target site due to rapid degradation in vivo.…”
Section: Introductionmentioning
confidence: 99%